PENGARUH GAYA KEPEMIMPINAN, KEMAMPUAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) BHAKTI SUMEKAR SUMENEP - jurnalmap map; Cahya Wiratama; Wasis Budiarto; Indra Prasetyo (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This research was conducted at the Sharia Community Financing Bank (BPRS) Bhakti Sumekar Sumenep with a total sample of 60 people (sampling technique was random sampling). The purposes of this study are: 1) To describe the leadership style, ability, work motivation and performance of employees, 2) To test and analyze whether the leadership style, ability and work motivation simultaneously have a significant influence on the performance of employees 3) To test and analyze whether leadership style, ability and work motivation partially have a significant influence on the performance of employees. Analysis of data using SPSS, this type of research is explanatory research using quantitative research approaches. The results of the study show that: 1) Simultaneously the leadership style, ability and motivation of work have an influence on the performance of employees, 2) Partially the leadership style, ability and motivation of work have an influence on the performance of employees. Keywords: Leadership Style (X1), Ability (X2), Motivation (X3) And Work Performance Of Employees (Y).